Design Of Personal Finance Management Application Based On Mobile App: Case Study Of Students Of STMIK Mardira Indonesia - Fitria, Desi; Mustari, Farhanah Fitria; Retnowaty, Agung Tri; Subagja, Roni Ilham (Informatics Management, Engineering and Information System Journal, 2025)
Personal financial management presents considerable difficulty for students, primarily due to limited income and frequently inconsistent lifestyles.  This research encompassed 60 students from STMIK Mardira Indonesia.  The questionnaire results indicated that 61.4% of respondents found it challenging to monitor their accounts constantly, and 21.4% expressed concerns about having insufficient time for documentation.  This research aims to develop a mobile application for personal money management specifically designed for students.  The application was developed using the Agile research methodology, utilizing AppSheet, and linked with Google Drive to guarantee data security.  The study utilized data collection techniques, including questionnaires, interviews, and literature reviews.  The results demonstrate that this program is proficient in aiding students with transaction documentation, budget oversight, and improving their financial literacy.  It is advisable to have functionalities for visualizing financial information and implementing automatic notifications when expenditures are near the established budget threshold.